Women in Construction Boots: The Enabling Factors from the Perspective of Female Adolescents - Abdul Majid, Masidah; Mohamed Yusoff, Wardah Fatimah; Sapian, Abdul Razak (2020)
Shortage of local skilled workers still exists in the construction industry of Malaysia and this in general may affect its sustainability in the long term if the problem is allowed to continue. Presently, the main contractors have to employ foreign workers from less developed countries in order to fulfil the needs of manual manpower. However, the employment of foreign workers is not the solution which the country should adopt as their presence brings a lot of socio-economic problems. It is suggested that the industry should not only attract local male youth but start to encourage female to become construction skilled workers to widen up the pool of talents. The present paper reports the findings from a survey conducted among female adolescents in Selangor, Malaysia in order to have some understanding on what is the important factors that may attract female adolescents to consider to become construction skilled workers. A factor analysis has been performed and it is suggested that the policy makers should focus on these six important factors namely conviction, satisfaction, recognition, value, support and qualification factors in order to encourage more female local youth to become construction skilled workers